Navigating Factors Of Cloud Computing Adoption For Smes In Halal Food Industry - Farah Laili Muda @ Ismail; Anita Ismail; Umi Hamidaton Mohd Soffian Lee; Mohd Azmir Mohd Nizah; Marsita Md Nor (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA